2018
DOI: 10.1103/physrevx.8.031050
|View full text |Cite
|
Sign up to set email alerts
|

Theory for Swap Acceleration near the Glass and Jamming Transitions for Continuously Polydisperse Particles

Abstract: Swap algorithms can shift the glass transition to lower temperatures, a recent unexplained observation constraining the nature of this phenomenon. Here we show that swap dynamic is governed by an effective potential describing both particle interactions as well as their ability to change size. Requiring its stability is more demanding than for the potential energy alone. This result implies that stable configurations appear at lower energies with swap dynamics, and thus at lower temperatures when the liquid is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(74 citation statements)
references
References 53 publications
(86 reference statements)
6
68
0
Order By: Relevance
“…A truncated and discretized Gaussian size distribution with the same R as, but somewhat lower polydispersity δ = 7% than measured was used. Simple particle translations combined with swap moves [30] allow the efficient sampling of phase space up to high φ [31]. Simulations were run with N = 19 991 particles in a cubic box with periodic conditions.…”
Section: Relative Probabilitymentioning
confidence: 99%
“…A truncated and discretized Gaussian size distribution with the same R as, but somewhat lower polydispersity δ = 7% than measured was used. Simple particle translations combined with swap moves [30] allow the efficient sampling of phase space up to high φ [31]. Simulations were run with N = 19 991 particles in a cubic box with periodic conditions.…”
Section: Relative Probabilitymentioning
confidence: 99%
“…The theoretical understanding of the jamming of nonspherical particles is challenging because particles do not hold rotational symmetry. In the previous work [5,9], we proposed a way to bypass this difficulty by considering the mapping from nonspherical particles to the breathing particles (BP), defined as a system of spherical particles for which their diameters are allowed to fluctuate [10]. An advantage of the BP particles is that the model holds the rotational symmetry, and thus, one can apply the same technique developed for the spherical particle without any difficulty.…”
Section: Introductionmentioning
confidence: 99%
“…First, computer simulations studies [6] showed that particle size exchanges in systems with a continuous polydispersity result in the largest speed-up of the dynamics. Second, a system with a continuous polydispersity allows one to treat the particles' diameters as additional variables that evolve according to their own equation of motion [14]. The distribution of the particles diameters is then enforced by a diameter-dependent chemical potential-like term, which plays the role of an one-particle external potential for the diameter variable.…”
Section: Model: Binary Mixture With Particle Size Swapsmentioning
confidence: 99%
“…Next, Brito et al [14], in the context of continuous distribution of particles' diameters, proposed to treat the diameters as additional variables, endowed with their own equations of motion (stochastic in the case of the Monte Carlo dynamics and deterministic continuous time equations in the case of the Newtonian-like dynamics). This allowed Brito et al to put forward some general arguments, which imply that allowing particle size swaps should lead to the decrease of the onset temperature for the glassy dynamics.…”
Section: Introductionmentioning
confidence: 99%